2A(A-6)=0

Simple and best practice solution for 2A(A-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2A(A-6)=0 equation:


Simplifying
2A(A + -6) = 0

Reorder the terms:
2A(-6 + A) = 0
(-6 * 2A + A * 2A) = 0
(-12A + 2A2) = 0

Solving
-12A + 2A2 = 0

Solving for variable 'A'.

Factor out the Greatest Common Factor (GCF), '2A'.
2A(-6 + A) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'A' equal to zero and attempt to solve: Simplifying A = 0 Solving A = 0 Move all terms containing A to the left, all other terms to the right. Simplifying A = 0

Subproblem 2

Set the factor '(-6 + A)' equal to zero and attempt to solve: Simplifying -6 + A = 0 Solving -6 + A = 0 Move all terms containing A to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + A = 0 + 6 Combine like terms: -6 + 6 = 0 0 + A = 0 + 6 A = 0 + 6 Combine like terms: 0 + 6 = 6 A = 6 Simplifying A = 6

Solution

A = {0, 6}

See similar equations:

| 6(x+4)+5x=5(x+5)-7 | | 0.9p=5.4 | | 21=9a | | 2(X+3)-5(X+1)=0 | | b^2=21-10b | | x^2-12x-169=0 | | (X-0.5)*(X+2)=0 | | 2p=3p-5 | | 21+-1X+-1Y+5Y+20(1X+9)=351 | | (-2x^3+5x^2-x+7)+(4x^3-3x+2)= | | (8X-4)-(X+3)=0 | | 4a=-7a | | 5c+12=8c+10.23 | | -2x+4=x-6 | | 1(x+6)+4=7(x-2) | | (9A+7)+(5A-6)=0 | | 17x+3y=13 | | 10m^2+3m-21=0 | | q=1/3mr | | 21-2/7 | | X+y+1x+9=30 | | x+2y+4z=7 | | -3+5x-4+2x=-5x-5-9x | | -4(y+3)=4y-4+2(3y+1) | | 5n-3=2n-9 | | 72x=3 | | -4(-4w+2)-3w=3(w-3)-5 | | 2a+9d=47 | | 9=16+(-1r) | | t(8t+3)=0 | | 54=-u+280 | | log(5)(x+8)+log(5)(x+4)=1 |

Equations solver categories